β-caryophyllene sensitizes hepatocellular carcinoma cells to chemotherapeutics and inhibits cell malignancy through targeting MAPK signaling pathway - Basheer, Irum; Wang, Hai; Li, Guangyue; Jehan, Shah; Raza, Ali; Du, Chentao; Ullah, Najeeb; Li, Dangdang; Sui, Guangchao (Frontiers in Pharmacology, 2024)
Backgroundβ-caryophyllene (BCP) is a naturally occurring bicyclic sesquiterpene extracted from various plants, and widely used as a medicinal agent for various diseases. During hepatocellular carcinoma (HCC) development, cancer cells generally exhibit increased cell proliferation due to mutations or aberrant expression of key regulatory genes. The current study determines the cytotoxic effects of BCP alone or in combination with doxorubicin (DOX) and cisplatin (DDP) on HCC cells, and elucidates the underlying mechanism of BCP to exert its anticancer activities.Materials and methodsHepG2, SMMC-7721 HCC cells, and HL-7702 normal liver cells were treated with BCP, DOX, and DDP individually or combinatorially. Cell proliferation assay, flow cytometric assay, and Western blot were employed to evaluate the cytotoxic effects of these treatments. Transwell assays were used to examine BCP’s effects on HCC cell migration and invasion. RNA-seq analysis was used to determine BCP’s primary target genes in HepG2 cells. Integrative analysis of differentially expressed genes (DEGs) of RNA-seq data with an HCC TCGA dataset identified BCP-targeted genes that were verified by RT-qPCR analysis. Ectopic gene expression, cell viability, and colony formation assay were performed to validate the primary targets of BCP.ResultsBCP selectively inhibited HCC cell proliferation while exhibited relatively low toxicity in normal liver cells; however, DOX and DDP showed higher toxicity in normal cells than that in HCC cells. In combinatorial treatments, BCP synergistically enhanced cytotoxicity of DOX and DDP in HCC cells but this effect was markedly reduced in HL-7702 cells. BCP treatment reduced migration and invasion of HCC cells. Furthermore, RNA-seq analyses of BCP-treated HepG2 cells identified 433 protein-coding DEGs. Integrative analyses revealed five BCP-targeted DEGs regulating the MAPK signaling pathway. Among these five genes, three displayed a significantly positive correlation of their expression with the overall survival of HCC patients. As a primary target, PGF was significantly downregulated by BCP treatment, and its exogenous expression desensitized HCC cells to BCP-mediated inhibition.DiscussionBCP inhibits malignant properties of HCC and synergistically sensitizes the anticancer activity of DOX and DDP. In HCC cells, BCP primarily targets the PGF gene and MAPK signaling pathway.